Facile Electron Transfer in Atomically Coupled Heterointerface for Accelerated Oxygen Evolution. Issue 1 (10th November 2022) - Ibrahim, Kassa Belay; Shifa, Tofik Ahmed; Moras, Paolo; Moretti, Elisa; Vomiero, Alberto
Abstract: An efficient and cost‐effective approach for the development of advanced catalysts has been regarded as a sustainable way for green energy utilization. The general guideline to design active and efficient catalysts for oxygen evolution reaction (OER) is to achieve high intrinsic activity and the exposure of more density of the interfacial active sites. The heterointerface is one of the most attractive ways that plays a key role in electrochemical water oxidation. Herein, atomically cluster‐based heterointerface catalysts with strong metal support interaction (SMSI) between WMn2 O4 and TiO2 are designed. In this case, the WMn2 O4 nanoflakes are uniformly decorated by TiO2 particles to create electronic effect on WMn2 O4 nanoflakes as confirmed by X‐ray absorption near edge fine structure. As a result, the engineered heterointerface requires an OER onset overpotential as low as 200 mV versus reversible hydrogen electrode, which is stable for up to 30 h of test. The outstanding performance and long‐term durability are due to SMSI, the exposure of interfacial active sites, and accelerated reaction kinetics. To confirm the synergistic interaction between WMn2 O4 and TiO2, and the modification of the electronic structure, high‐resolution transmission electron microscopy (HR‐TEM), X‐ray photoemission spectroscopy (XPS), and X‐ray absorption spectroscopy (XAS) are used. Abstract : An atomically thin heterointerface catalyst with strong metal support interaction (SMSI) between WMn2 O4 and TiO2 is designed. WMn2 O4 nanoflakes are uniformly and densely decorated by TiO2 particles to modulate the electronic band structure. The engineered heterointerface requires an oxygen evolution reaction (OER) onset overpotential as low as 200 mV vs RHE, which is stable for up to 30 h of test, among the most effective OER electrocatalysts.